Advances in nitrogen-containing helicenes: synthesis, chiroptical properties, and optoelectronic applications - Meng Qiu; Jing Du; Nai-Te Yao; Xin-Yue Wang; Han-Yuan Gong (Beilstein Journal of Organic Chemistry)
Helicenes, a class of non-planar polycyclic aromatic hydrocarbons composed of ortho-fused aromatic rings forming helical architectures, have attracted considerable attention due to their intrinsic chirality and tunable optoelectronic properties. Among them, nitrogen-doped helicenes (azahelicenes) and their heteroatom-co-doped counterparts – such as B/N-, O/N-, S/N-, and Se/N-doped helicenes – have emerged as highly versatile scaffolds for chiral optoelectronic applications. The incorporation of nitrogen enables precise modulation of electronic structures, redox characteristics, and intermolecular interactions, thereby enhancing performance in circularly polarized luminescence (CPL), thermally activated delayed fluorescence (TADF), and chiral sensing. Notably, recent developments have yielded π-extended, structurally robust, and stimuli-responsive azahelicenes exhibiting record-high dissymmetry factors (|gabs| and |glum|), elevated CPL brightness (BCPL), and efficient integration into CPL-OLEDs and redox-switchable emitters. Boron–nitrogen co-doping strategies, in particular, have facilitated the development of materials with ultra-narrowband emissions, near-unity photoluminescence quantum yields, and electroluminescence dissymmetry factors (|gEL|) exceeding 10−3. Likewise, heteroatom co-doping with oxygen, sulfur, or selenium enables spectral tuning across the visible to near-infrared range, improved photostability, and dual-state emissive behavior. In parallel, significant progress in synthetic methodologies – including enantioselective catalysis, electrochemical cyclizations, and multicomponent reaction systems – has granted access to increasingly complex helicene frameworks with well-defined chirality. This review systematically summarizes recent advancements in the synthesis, structural engineering, and chiroptical performance of nitrogen-doped helicenes and their heteroatom-doped derivatives, emphasizing their potential as next-generation chiral optoelectronic materials and outlining future directions toward multifunctional integration and quantum technological applications.